If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = 5n + n Combine like terms: 5n + n = 6n 12 = 6n Solving 12 = 6n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-6n' to each side of the equation. 12 + -6n = 6n + -6n Combine like terms: 6n + -6n = 0 12 + -6n = 0 Add '-12' to each side of the equation. 12 + -12 + -6n = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -6n = 0 + -12 -6n = 0 + -12 Combine like terms: 0 + -12 = -12 -6n = -12 Divide each side by '-6'. n = 2 Simplifying n = 2
| 25-w=5w | | 3(k+8)+6=15 | | 6x+2=-3+7x | | x+1-(-x)=x | | 3/-5b-1/10=7/20-7/10b | | -10=-(m+6) | | 2k^2-50=0 | | (7x-7)(x+5)= | | x-1=6x-31 | | 2x-3=x2/3 | | 5=-3n-1+n | | V=-2v+80 | | tan(50)=x/20 | | -x+6=-8+6x | | f(x)=(x+2)(x+1)(x-5) | | 2(h-4)=8 | | 8(t-4)=40 | | 10n-2-3n=19 | | 3+3n+4=16 | | -3(6+3k)=-18+7k | | 2x-1=5x+6 | | 8y-6y=12-8 | | 4(x+1)+2x=4+x+1+4+1+2+x+2+2 | | 1/2x26 | | -3k-34=4(k-5) | | 2x-3+4x=15 | | 9+5m=-6 | | .17x-0.43=.25k+0.05 | | 50=x-(x*0.054+0.3) | | 0=-5v-4v | | -8(1+3x)=40-8x | | 2n-126=-4n |